Modern Information Technologies in Teaching the Discipline Engineering Geodesy - Gulbayev N.A. (Global Scientific Publishing, 2022)
At the present stage of development of the country is carried out modernization of higher education, in which teachers are actively being sought new approaches, tools and methods. The purpose of educational activities aimed at improving the quality of education through the adoption and integration of modern educational technologies. This article explores ways of forming knowledge and skills of future engineers in the study course "Engineering Surveys" with the use of information technology
Keywords: modernization of higher education; quality of education; surveying